Altitude on the physicochemical characteristics of coffee beverage from beans produced in Taquaritinga do Norte, in the state of Pernambuco, Brazil - Vilela Santos, Wallysson Wagner; Santos Silva, Gustavo Henrique Daniel; Rabêlo da Silva, Elisandra; Bezerra de Lima e Silva, Mateus; Lira de Oliveira, Rodrigo; Pedroza da Silva, Suzana (Pesquisa Agropecuaria Brasileira, 2025)
The objective of this work was to determine the physicochemical characteristics of coffee beverages prepared with Coffea arabica beans produced at different altitudes in the municipality of Taquaritinga do Norte, in the state of Pernambuco, Brazil. Eight coffee bean samples, obtained from five different producers, were analyzed in a completely randomized design, with three replicates. The evaluated variables were: total acidity, pH, electrical conductivity, total dissolved solids, extraction percentage, reducing sugars, and caffeine content. The data were subjected to the analysis of variance, Tukey’s mean test, and agglomerative hierarchical clustering. The results showed total acidity from 0.39 to 3.05 mL-1 NaOH, pH from 5.30 to 4.80, electrical conductivity from 2.79 to 3.24 µS cm-1, total dissolved solids from 2.00 to 2.56 °Brix, extraction percentage from 18.14 to 27.24%, reducing sugars from 0.28 to 0.40%, and caffeine content from 0.50 to 2.18%. Through agglomerative hierarchical clustering, two groups of samples were discriminated based on the evaluated physicochemical parameters. Altitude is a common aspect of the samples of a same group, defining different characteristics of coffee beverages in Taquaritinga do Norte.